Efeito da estimula????o transcraniana por corrente cont??nua associada ao treino de marcha sobre o equil??brio e o desempenho funcional de crian??as com paralisia cerebral: ensaio cl??nico controlado aleatorizado e duplo cego - Duarte, Nat??lia de Almeida Carvalho (2015)
The goal of this study was to Investigate the effects of transcranial direct current stimulation in the primary motor cortex, associated with gait training on balance and functional performance of children with cerebral palsy (CP). The sample population that was part of this project consisted of 24 children with CP between five and ten years old. Children were be randomly allocated into two groups (Group 1: gait training on the treadmill with transcranial stimulation activates, Group 2: gait training on the treadmill with transcranial stimulation placebo) and evaluated at three different times (pre-intervention, immediately after and one month after the proposed training). The evaluation consisted of the quantification of static balance, functional balance (Pediatric Balance Scale) and functional performance (Inventory assessment of pediatric disorders). The trainings was done for two consecutive weeks, with five training sessions per week, for 20 minutes per session. The transcranial stimulation and treadmill training was realized simultaneously, in each session during twenty minutes, with an intensity of 1 mA. The results were statistically analyzed assuming a significance level of 0.05 (p < 0.05). The experimental group exhibited better results in comparison to the control group with regard to anteroposterior sway (eyes open and closed; p,0.05), mediolateral sway (eyes closed; p,0.05) and the Pediatric Balance Scale both one week and one month after the completion of the protocol. Gait training on a treadmill combined with anodal stimulation of the primary motor cortex led to improvements in static balance and functional performance in children with cerebral palsy.